Meru co-ordinates spindle orientation with cell polarity and cell cycle progression. - McLellan, M.M.; Aerne, B.L.; Banerjee Dhoul, J.J.; Holder, M.V.; Auchynnikava, T.; Tapon, N. (The EMBO Journal, 2025)
Correct mitotic spindle alignment is essential for tissue architecture and plays an important role in cell fate specification through asymmetric cell division. Spindle tethering factors such as Drosophila Mud (NuMA in mammals) are recruited to the cell cortex and capture astral microtubules, pulling the spindle in the correct orientation. However, how spindle tethering complexes read the cell polarity axis and how spindle attachment is coupled to mitotic progression remains poorly understood. We explore these questions in Drosophila sensory organ precursors (SOPs), which divide asymmetrically to give rise to epidermal mechanosensory bristles. We show that the scaffold protein Meru, which is enriched at the posterior cortex by the Frizzled/Dishevelled planar cell polarity complex, in turn recruits Mud, linking the spindle tethering and polarity machineries. Furthermore, Cyclin A/Cdk1 associates with Meru at the posterior cortex, promoting the formation of the Mud/Meru/Dsh complex via Meru and Dsh phosphorylation. Thus, Meru couples spindle orientation with cell polarity and provides a cell cycle-dependent cue for spindle tethering.